Study of the Effect of Methyl Eugenol on Gastric Damage Produced by Spinal Cord Injury Model in the Rat - Leticia Cruz-Antonio; María Elena Sánchez-Mendoza; Jazmín García-Machorro; Yaraset López-Lorenzo; Jesús Arrieta (Molecules)
Traumatic spinal cord injury (SCI) is a serious medical condition that places patients at high risk of developing gastric ulceration and gastrointestinal bleeding. One preventative strategy involves the use of omeprazole; however, its chronic use is associated with adverse effects, highlighting the need for alternative therapies. This study evaluated the protective effects of methyl eugenol (ME) on gastric mucosal damage in a rat model of SCI. ME was administered orally at doses of 30, 100, and 177 mg/kg in SCI induced at the T9 level, alongside diclofenac or ketorolac (30 mg/kg each). The enzymatic activity of superoxide dismutase, catalase, and glutathione peroxidase was assessed, and the levels of total glutathione and malondialdehyde were determined using biochemical kits. Additionally, stomach histological sections were analyzed. ME exhibited dose-dependent gastroprotective effects, with maximal protection observed at 177 mg/kg in the presence of diclofenac (9.78 ± 2.16 mm2) or ketorolac (12.49 ± 2.17 mm2). A histological analysis confirmed these findings. In conclusion, methyl eugenol protects the gastric mucosa from SCI-induced damage, with glutathione peroxidase and catalase playing key roles in its mechanism of gastroprotection.